ANALISIS TECHNOLOGY ACCEPTANCE MODEL (TAM) SISTEM INFORMASI AKADEMIK (SIAKAD) INSTITUT TEKNOLOGI DAN BISNIS BANTEN - Khabi Bunajjar; Toni Fathoni; Nastiti Tri Permatasari (Jurnal Komunikasi, 2025)
This study analyzes the influence of Perceived Ease of Use, Perceived Usefulness, and System Security on User Satisfaction with the Academic Information System (SIAKAD) at the Institut Teknologi dan Bisnis Banten. Using a quantitative approach with a Likert-scale questionnaire (1–5), the results show average scores of 4.05, 4.12, 3.45, and 3.78 for each variable, respectively. The regression model Y=0.322X1+0.284X2+0.301X3+eY = 0.322X_1 + 0.284X_2 + 0.301X_3 + eY=0.322X1 +0.284X2+0.301X3+e obtained an R² value of 0.612, indicating that 61.2% of user satisfaction variation is explained by the three independent variables. Both t-test and F-test results show positive and significant effects (p < 0.05). The findings confirm that ease of use, usefulness, and system security significantly improve student satisfaction. This study extends the Technology Acceptance Model (TAM) by adding security as an external factor and recommends enhancing system stability, data protection, and digital infrastructure to increase user trust and satisfaction